1994
DOI: 10.1182/blood.v84.4.1031.bloodjournal8441031
|View full text |Cite
|
Sign up to set email alerts
|

Activated protein C resistance as an additional risk factor for thrombosis in protein C-deficient families

Abstract: Heterozygous protein C deficiency is associated with an increased risk for thrombosis. This association is restricted to a minority of protein C-deficient families, which have been defined as clinically dominant protein C-deficient. In contrast, in the clinically recessive protein C- deficient families, only the homozygous family members are (severely) affected. One possible explanation for this difference in thrombotic risk between families may be the presence of a second hereditary risk factor. A good candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
155
1
6

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(172 citation statements)
references
References 0 publications
10
155
1
6
Order By: Relevance
“…Factor V Leiden was found in 20% and 39% of thrombophilic families with deficiencies of protein C and protein S, respectively. Relatives with multiple thrombophilic disorders had a significantly higher incidence of VTE (72%) than those with protein C deficiency (31%) or protein S deficiency (19%) alone (15,16). Similar gene-gene interactions occur in families with inherited antithrombin deficiency (17).…”
Section: Gene-gene Interactionsmentioning
confidence: 88%
“…Factor V Leiden was found in 20% and 39% of thrombophilic families with deficiencies of protein C and protein S, respectively. Relatives with multiple thrombophilic disorders had a significantly higher incidence of VTE (72%) than those with protein C deficiency (31%) or protein S deficiency (19%) alone (15,16). Similar gene-gene interactions occur in families with inherited antithrombin deficiency (17).…”
Section: Gene-gene Interactionsmentioning
confidence: 88%
“…The only child heterozygous for the factor V Leiden mutation did have thrombosis in association with an indwelling venous catheter. It has been suggested that the factor V Leiden mutation may be a cofactor for thrombosis in association with other haemostatic abnormalities or prothrombotic conditions (Nowak-Gottl et al, 1995;Petaja et al, 1995;Zoller et al, 1995a, b;Koeleman et al, 1994;Gandrille et al, 1995). Indwelling central venous catheters are often associated with thrombotic events ( Johnston-Anderson et al, 1989;Moss et al, 1989;Mueller et al, 1992;David & Andrew, 1993;Krafter-Jacobs et al, 1995), even in the absence of other obvious risk factors for thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that combined FVIII and FXI deficiency is associated with more severe bleeding manifestations than those found when the defects are present separately [1]. Families with factor V (FV) Leiden and protein C deficiency are more prone to thrombophilia than are those patients with only one of these defects [2]. Accordingly, concomitant mutations in two coagulation genes or two thrombotic genes can worsen the clinical severity of their respective clinical pictures.…”
Section: Bleeding Manifestationsmentioning
confidence: 99%